2022
DOI: 10.1029/2022gl097757
|View full text |Cite
|
Sign up to set email alerts
|

Empirically Determined Auroral Electron Events at Mars—MAVEN Observations

Abstract: Discrete aurorae have been observed at magnetized planets such as Earth and Jupiter, triggered by accelerated electrons. Similar aurorae have also been observed at Mars with only localized strong crustal magnetisms. However, our understanding of this phenomenon at Mars is still limited. In particular, direct and quantitative comparisons of the auroral and its source electron events are lacking as these two types of observations are usually made at different times and/or locations. In this study, we establish e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 49 publications
4
23
0
Order By: Relevance
“…Building on Xu et al. (2022), we apply the same selection criteria to identify auroral electrons and determine how the upstream drivers affect their occurrence rates and also the integrated electron fluxes. Furthermore, auroral electron impact can cause effects other than observable auroral emission, one of which is the enhanced local ionization and thus local ion densities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Building on Xu et al. (2022), we apply the same selection criteria to identify auroral electrons and determine how the upstream drivers affect their occurrence rates and also the integrated electron fluxes. Furthermore, auroral electron impact can cause effects other than observable auroral emission, one of which is the enhanced local ionization and thus local ion densities.…”
Section: Discussionmentioning
confidence: 99%
“…Discrete aurora and its source electrons have both been observed and studied at Mars. Building on Xu et al (2022), we apply the same selection criteria to identify auroral electrons and determine how the upstream drivers affect their occurrence rates and also the integrated electron fluxes. (d) The ratio between median ion densities measured when integrated electron fluxes are above and below 1.1 × 10 10 eV cm −2 s −1 sr −1 , different colors for different ion species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within this region, discrete aurora occurs more frequently on the dusk side and for westward interplanetary magnetic field (IMF) directions (Schneider et al, 2021) with no significant dependence on local time or IMF direction in other regions. Xu et al (2022) showed that accelerated electron events share the same characteristics (locations, crustal field, etc.) as the auroral events, establishing a causal connection.…”
Section: Supporting Informationmentioning
confidence: 99%